2021
DOI: 10.1016/j.jaci.2020.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Incidence rates of hospitalization and death from COVID-19 in patients with psoriasis receiving biological treatment: A Northern Italy experience

Abstract: Introduction: Whether biologic therapies enhance the risk of coronavirus 2019 or affect the disease outcome in patients with chronic plaque psoriasis remains to be ascertained. Objective: We sought to investigate the incidence of hospitalization and death for COVID-19 in a large sample of patients with plaque psoriasis receiving biologic therapies compared with the general population. Methods: This is a retrospective multicenter cohort study including patients with chronic plaque psoriasis (n 5 6501) being tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 9 publications
3
44
0
2
Order By: Relevance
“…In addition, there was no significant increased risk of hospitalization associated with COVID-related interstitial pneumonia. These observations have been confirmed in other studies [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. PsoProtect (Psoriasis Patient Registry for Outcomes, Therapy and Epidemiology of Covid-19 infecTion) is an international web-based registry (www.psoprotect.org) for healthcare providers to report outcomes of COVID-19 in individuals with psoriasis [ 70 ].…”
Section: Biologics For Psoriasissupporting
confidence: 88%
“…In addition, there was no significant increased risk of hospitalization associated with COVID-related interstitial pneumonia. These observations have been confirmed in other studies [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. PsoProtect (Psoriasis Patient Registry for Outcomes, Therapy and Epidemiology of Covid-19 infecTion) is an international web-based registry (www.psoprotect.org) for healthcare providers to report outcomes of COVID-19 in individuals with psoriasis [ 70 ].…”
Section: Biologics For Psoriasissupporting
confidence: 88%
“…Moreover, Cho et al concluded in their epidemiological study that biologics for dermatological conditions did not seem to influence the susceptibility or mortality related to COVID-19, suggesting that biologics might be continuously used during the COVID-19 pandemic (63). As proof of this, Gisondi et al found no negative impact of biologics on COVID-19 outcome in patients with psoriasis and did not advise discontinuation of biologic treatment of psoriasis to reduce the risk of SARS-CoV-2 infection (67). Data on a small cohort of patients with moderate-to-severe atopic dermatitis treated with dupilumab, a monoclonal antibody inhibiting the shared receptor component for IL-4 and IL-13, also suggest no increased risk for COVID-19 in this subset (55).…”
Section: Cutaneous Diseasesmentioning
confidence: 99%
“…Our patient was on Methotrexate (immune‐suppressant) for his psoriasis, with the last dose taken two weeks before hospitalization. A multi‐center study in Italy found that the incidence rate of death due to COVID‐19 disease was lower in patients with psoriasis (under biological therapy) than in general population, suggesting no need of discontinuing ongoing therapy 16 . Additionally, during hospitalization, the patient was treated with higher than normal dose of prophylactic anticoagulant (Enoxaparin 80mg q24h) 17 .…”
Section: Discussionmentioning
confidence: 99%